Seasonal Variation of 'Candidatus Liberibacter asiaticus' Titers in New Shoots of Citrus in Distinct Environments - Lopes, Silvio A.; Luiz, Fernanda Q. B. F.; Oliveira, Hermes T.; Cifuentes-Arenas, Juan C. [UNESP]; Raiol-Junior, Laudecir L. [UNESP] (Amer Phytopathological Soc, 2017)
The major citrus area of Brazil occupies near 450,000 ha between the Triangulo Mineiro (TM) region of Minas Gerais State and the south of Sao Paulo State (SPS). Significant climatic variation occurs between regions which could affect huanglongbing (HLB) progress, which is lower in TM. To investigate this possibility, young sweet orange shoots were sampled periodically over 2 years to determine 'Candidatus Liberibacter asiaticus' titers in naturally infected trees in orchards in Analandia, central SPS, and Frutal and Comendador Gomes, within TM. Data-loggers recorded local temperature and relative humidity hourly. In the laboratory, five 'Ca. L. asiaticus'-free Diaphorina citri adults were placed on each sampled shoot for 48 h to feed and acquire the pathogen. Shoots and insects were individually analyzed by quantitative polymerase chain reaction to determine 'Ca. L. asiaticus' titers. The incidence of 'Ca. L. asiaticus'-positive shoots, 'Ca. L. asiaticus' titers, and acquisition rates were lower for shoots from Comendador Gomes than those from Frutal or Analandia Stronger association was observed between 'Ca. L. asiaticus' titers and the number of hours below 15 degrees C (h < 15 degrees C) or above 30 degrees C (h > 30 degrees C), and cumulative rainfall registered during the 15 days prior to sampling of shoots on each occasion. 'Ca. L. asiaticus' titers associated positively with h < 15 degrees C and rainfall and negatively with h > 30 degrees C. The slower spread and lower incidence of HLB in TM may be related to lower incidences of 'Ca. L. asiaticus'-positive young shoots and lower titers of 'Ca. L. asiaticus' in the same shoots as a consequence of the warmer and drier conditions.